Participation of Youth in Rural Leadership Development Activities in Yewa South Local Government Area of Ogun State, Nigeria - Agbelemoge, Adeyanju; Adebanjo, S.A (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> The focus of the study was to assess the levels of participation of youth in rural leadership development activities in Yewa South Local Government Area of Ogun State, Nigeria. Purposive and systematic random sampling techniques were adopted for the study. This study considered the socio-economic characteristics of the rural youth, stages of participation in rural leadership development activities, motivational factors influencing youth`s participation and constraints to participation in rural leadership development activities. Structured interviewed scheduled were administered on 108 youths within the age of 18 – 35. Descriptive statistical techniques like frequency counts and percentage were used to analyse the data. Inferential statistics like chi-square test was used to determine the relationship between variables investigated in the study. The study revealed that 57.05% had low participation 29.42% had moderate participation and 13.53% of them had high participation in rural leadership development activities. Results of the hypothesis testing revealed that at 5% level of confidence, significant relationship existed between sex (X2 = 59.4), level of education (X2 = 67.0), religion (X2 = 46.5), marital status (X2 = 35.87), Length of residency (X2 =35.01), level of education (X2 = 35.01) membership of community association (X2 =70.74), motivational factors (X2 = 48.60) and stages of participation while no significant relationship exist between age (X2 = 2.2) and stages of participation while no significant relationship exist between age. Conclusively, rural youth should be adequately motivated and oriented by the extension agents and community development workers in order to make them productive to themselves, to the rural community and bring about community development. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0in; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->